2016
DOI: 10.1007/s10509-016-2859-0
|View full text |Cite
|
Sign up to set email alerts
|

Extensive photometry of the intermediate polar MU Cam: detection of a spin period change

Abstract: Intermediate polars with known rates of spin period changes are not numerous because such tasks require measurements performed for a long time.To measure a spin period change, MU Cam is a good candidate because it has a spin oscillation with a large amplitude enabling measurements with high precision. Fortunately, in the past the spin period of MU Cam was measured with high precision. To measure the spin period anew, in 2014-2015 we performed extensive photometric observations of MU Cam, spanning a total durat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
2
1
Order By: Relevance
“…From the rms error of the spin period, we found that the formal validity of this ephemeris is equal to 36 years (a 1σ confidence level). Although this formal validity seems large, it is noticeably less than the formal validities of the spin ephemerides, which we obtained for V455 And, V647 Aur and MU Cam (85-100 years) by applying roughly the same observational coverage (Kozhevnikov 2012(Kozhevnikov , 2014(Kozhevnikov , 2016. The reason consists in noticeably less amplitude of the spin oscillation in V2069 Cyg.…”
Section: Analysis and Resultscontrasting
confidence: 59%
See 1 more Smart Citation
“…From the rms error of the spin period, we found that the formal validity of this ephemeris is equal to 36 years (a 1σ confidence level). Although this formal validity seems large, it is noticeably less than the formal validities of the spin ephemerides, which we obtained for V455 And, V647 Aur and MU Cam (85-100 years) by applying roughly the same observational coverage (Kozhevnikov 2012(Kozhevnikov , 2014(Kozhevnikov , 2016. The reason consists in noticeably less amplitude of the spin oscillation in V2069 Cyg.…”
Section: Analysis and Resultscontrasting
confidence: 59%
“…Spin oscillations of many IPs are directly visible in the light curves (see, e.g., figure 1 in Kozhevnikov 2016). In contrast, the oscillation of V2069 Cyg with a period of about 743 s, which is detected in X-rays and in optical light and obviously corresponds to the spin period (Bernardini et al 2012), is inconspicuous in the light curves (Fig.…”
Section: Analysis and Resultsmentioning
confidence: 97%
“…12 in Patterson 1994), they must have large amplitudes. The spin oscillation in V1033 Cas was the strongest oscillation compared with the oscillations in the 7 later discovered IPs, which we observed by using the same technique (Kozhevnikov 2001(Kozhevnikov , 2010(Kozhevnikov , 2012(Kozhevnikov , 2014(Kozhevnikov , 2015(Kozhevnikov , 2016(Kozhevnikov , 2017. Indeed, among these 7 IPs, only MU Cam revealed a bit lesser semi-amplitude of 90 mmag.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, MU Cam shows orbital variations with a similar semi-amplitude of 42-59 mmag (see Fig. 5 in Kozhevnikov 2016). The similar amplitudes of orbital variations in V1033 Cas and in MU Cam can mean that the inclinations of these two systems are also similar.…”
Section: Discussionmentioning
confidence: 73%